2020
DOI: 10.3390/ma13122714
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure Evolution and Performance Improvement of Hypereutectic Al–Mg2Si Metallic Composite with Ca or Sb

Abstract: In this article, the modification effects on Al–Mg2Si before and after heat treatment were investigated with Ca, Sb, and (Ca + Sb). In comparison with single Ca or Sb, the samples with composition modifiers (Ca + Sb) had the optimal microstructure. The sample with a molar ratio for Ca-to-Sb of 1:1 obtained relatively higher properties, for which the Brinell hardness values before and after heat treatment were remarkably increased by 31.74% and 28.93% in comparison with bare alloy. According to differential sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 40 publications
(41 reference statements)
0
1
0
Order By: Relevance
“…According to the previous researches, it was found that the molar ratio of Ca and Sb had a significant influence on the composite modification effect on Al–Mg 2 Si alloys and the optimum molar ratio of Ca and Sb was reported to be 1:1. [ 23 ] In our research, a novel Al–3.3Ca–10Sb masteralloy containing AlCa 11 Sb 9 and CaSb 2 particles was successfully synthesized and its composite modification effect on the microstructure evolution and mechanical properties of Al–Mg 2 Si alloy was analyzed in detail. Furthermore, the composite modification mechanism of this novel masteralloy was also discussed.…”
Section: Introductionmentioning
confidence: 99%
“…According to the previous researches, it was found that the molar ratio of Ca and Sb had a significant influence on the composite modification effect on Al–Mg 2 Si alloys and the optimum molar ratio of Ca and Sb was reported to be 1:1. [ 23 ] In our research, a novel Al–3.3Ca–10Sb masteralloy containing AlCa 11 Sb 9 and CaSb 2 particles was successfully synthesized and its composite modification effect on the microstructure evolution and mechanical properties of Al–Mg 2 Si alloy was analyzed in detail. Furthermore, the composite modification mechanism of this novel masteralloy was also discussed.…”
Section: Introductionmentioning
confidence: 99%